Comparative study of design methods for bolted flanges subjected to external loading - Ovalekar, Jay M.; Raykar, N.R.; Mohan, P. Murali (Materials today : proceedings, 2020)
Bolted flange leak tightness evaluation has been an involved topic and design calculations are further complicated in the presence of external loads. The present work compares three design methods used for incorporating effect of external loads in flange design: ASME BPVC, ASME Code Case, and equivalent pressure method. Total 35 flanges of different standard sizes and rating classes are analyzed in this study. For each case, maximum allowable external loads are computed by each of the three methods. Based on the results obtained from this study, practical guidelines are developed which will help practicing engineers to select an appropriate method to meet a specific design requirement.